Prevalence of risk and factors associated with obstructive sleep apnea‐hypopnea syndrome in an adult population in Kinshasa, Democratic Republic of Congo. (27th May 2022) - Tete, Boniface; Albdewi, Mohamad Ammar; Nkodila, Aliocha; Muhala, Blaise; Akilimali, Pierre; Bisuta, Serge; Makulo, Jean Robert; Kayembe, Jean Marie
Summary: Obstructive sleep apnea‐hypopnea syndrome (OSAHS) is an underdiagnosed and lesser known disease in sub‐Saharan Africa. We believe that this is the first descriptive and analytical cross‐sectional study in Kinshasa (from February 1 to October 31, 2021), which included respondents aged ≥18 years. The study aimed to determine the prevalence of the risk and factors associated with OSAHS. Each participant signed a free and informed consent. Statistical analyses were performed using XLStat 2020 and the Statistical Package for the Social Sciences version 24 for Windows. Odds ratios (ORs) were calculated to determine the degree of association between these variables and a high risk of OSAHS. The significance threshold was p < 0.05 and confidence interval (CI) at 95%. There were 4, 162 participants, including 2, 287 men (54.9%), with an mean (SD) age of 32 ± 12.6 years. The prevalence of OSAS risk was 17.4% and 7.9% for men and women, respectively. The associated risk factors were male sex (OR 4, 95% CI 3.20–5.54), hypertension (OR 6.7, 95% CI 4.87–9.30), age ≥60 years (OR 8.7, 95% CI 4.07–18.88), obesity/overweight (OR 1.94, 95% CI 1.13–3.78), and excessive daytime sleepiness (OR 2.63, 95% CI 2.05–3.56). The risk of OSAS in Kinshasa is high and it increases with age, male sex, obesity, and hypertension. The Snoring, Tiredness, Observed apnea, high blood Pressure, Body mass index, Age, Neck circumference, and male Gender (STOP‐BANG) questionnaire is an easy‐to‐use tool for diagnostic orientation.